Hierarchical Porous Molybdenum Carbide Based Nanomaterials for Electrocatalytic Hydrogen Production - Liu, Yan; Huo, Juanjuan; Guo, Jiaojiao; Lu, Li; Shen, Ziyan; Chen, Weihua; Liu, Chuntai; Liu, Hao (Frontiers in Chemistry, 2020)
The electrocatalytic hydrogen evolution reaction (HER) for the preparation of hydrogen fuel is a very promising technology to solve the shortage of hydrogen storage. However, in practical applications, HER catalysts with excellent performance and moderate price are very rare. Molybdenum carbide (MoxC) has attracted extensive attention due to its electronic structure and natural abundance. Here, a comprehensive review of the preparation and performance control of hierarchical porous molybdenum carbide (HP-MoxC) based catalysts is summarized. The methods for preparing hierarchical porous materials and the regulation of their HER performance are mainly described. Briefly, the HP-MoxC based catalysts were prepared by template method, morphology‐conserved transformations method, and secondary conversion method of an organic-inorganic hybrid material. The intrinsic HER kinetics are enhanced by the introduction of a carbon-based support, heteroatom doping, and the construction of a heterostructure. Finally, the future development of HP-MoxC based catalysts is prospected in this review.